Multiscale fracture mechanics model for the dorsal closure in Drosophila embryogenesis. (June 2019) - Gao, Yuan; Xue, Shi-Lei; Meng, Qinghua; Li, Bo; Feng, Xi-Qiao
Highlights: Multiscale crack-bridging model for the dorsal closure of Drosophila embryogenesis. A spatiotemporal cohesive law accounting for active contraction of cell protrusions. Stress intensity factors at the zipping tip induced by the active contraction forces. The model well predicts the tissue geometry and zipping speed during dorsal closure. Abstract: Dorsal closure is an essential developmental process of Drosophila embryogenesis, during which the ectoderm fuses the two sides of a gap into a complete ectodermal epithelium. A defective closure may cause scar formation or even embryonic lethality. In this paper, a multiscale fracture mechanics model is established by treating the dorsal closure as a crack healing process. We investigate how the F-actin dynamics at the subcellular level and the cell-pair fusion at the cellular level are orchestrated to accomplish the tissue-level closure. A spatiotemporal cohesive law is proposed to characterize the active contractions of filopodial and lamellipodial protrusions, which involve F-actin retrogradation. The contribution of active forces to dorsal closure is evaluated in terms of the stress intensity factors at the canthi of the gap. The proposed model can well predict both the evolutionary zipping zone shape and the sealing speed during dorsal closure, and the theoretical results are in consistency with relevant experiments. This work can not only elucidate the multiscale mechanisms underlying dorsal closure, but also provide a new perspective of facture mechanics to understand some physiological and pathological processes during the development of tissues and organs. Graphical abstract: A multiscale fracture mechanics model is established to elucidate the physical mechanisms in the dorsal closure of Drosophila embryogenesis which involves active contractions of filopodial and lamellipodial protrusions.Image, graphical abstract